FOREIGN TRADE ACTIVITY OF UKRAINE AND EGYPT - DYKHA, Mariia; DYKHA, Valerii; ELNASHAR, Elsayed A. (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the state and trends of Ukraine's foreign trade activity. The authors analyzed the volumes of Ukraine's exports and imports, the balance of Ukraine's foreign trade balance. The full-scale invasion of the Russian Federation into Ukraine led to a significant decrease in Ukraine's foreign trade turnover. Ukraine's exports decreased from 68,07 million USD in 2021 to 36,18 million USD in 2023. Imports decreased from 72,84 million USD in 2021 to 55,3 million USD in 2022. In 2023, import volumes increased to 63,57 million USD. During 2021-2023, Ukraine's foreign trade balance deteriorated (from -4,77 million USD to -27,39 million USD). The geographical structure of Ukraine's foreign trade was studied. The share of Ukraine's exports and imports with the countries of Europe, Asia, Africa, America, Australia and Oceania has been determined. The volumes of Ukraine's foreign trade turnover with African countries are not significant, however, among African countries, Egypt is Ukraine's leading foreign trade partner. The commodity structure of Ukraine's exports and imports as a whole has been analyzed, as well as the volumes of foreign trade turnover between Ukraine and Egypt. The groups of goods that predominate in Ukraine's exports and the groups of goods that enter Ukraine have been determined.It is noted that Ukraine and Egypt have great prospects for the development of cooperation. Ukraine seeks to build friendly strategic relations with the countries of the African continent, based on mutual respect for basic values and international principles. Egypt is interested in economic cooperation with Ukraine in innovative areas, such as IT, supply of railcar products, transport engineering, etc. Egypt is a popular destination for Ukrainian tourists. The resumption of air flights from Ukrainian cities will contribute to the intensification of tourist relations. Prospects for the development of foreign trade cooperation, scientific and technical, and cultural interaction between Ukraine and Egypt will be the subject of further research.
Keywords: Ukraine; Egypt; foreign trade activity; cooperation; export and import